CHEMICAL COMPOSITION OF UNRIPE ARABIC COFFEE (Coffea arabica L.) PROCESSED UNDER DRY AND WET CONDITIONS - Westin Nobre, Gilberto; Meira Borém, Flávio; Pedroza Isquierdo, Eder; Gualberto F. A. Pereira, Rosemary; Damasceno de Oliveira, Pedro (Coffee Science - ISSN 1984-3909, 2012)
This study was conducted in order to characterize the chemical composition and evaluate the quality of unripe coffeebeans, processed under dry and wet conditions, submitted to different periods of rest before peeling, with and without water. The coffeewas harvested, separated according to density and peeled. The experiment was conducted in a completely randomized design (CRD)with five repetitions and arranged in a factorial 3 x 2 x 2 (3 rest periods - 12, 24 and 48 hours, two types of processing - dry (naturalgreen) and wet (peeled green ); two rest conditions - presence and absence of water). Three additional treatments were also studied:control sample – unripe fruit produced during cherry peeling, natural unripe fruit (coffee that is not peeled) and peeled unripe fruit,processed immediately after harvest. The coffee was dried in thin layers on a concrete yard and turned every 30 minutes, and afterreaching a water content level of 30% (wb) was piled to complete drying. To evaluate quality, the following analysis were carried out:total sugars, reducing and not reducing, total acidity, soluble solids, potassium leaching, electrical conductivity and chlorogenic acids.It was observed that peeling of unripe fruits increases the physiological and chemical indicators of quality of unripe coffee and can beperformed immediately after peeling the ripe fruits, with no harm to quality. The use of water during the rest period of green fruit doesnot contribute to maintaining the quality of coffee, which can be dispensed when processing the green coffee